2006
DOI: 10.1002/app.25270
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐phase‐assisted surface polymerization of methyl methacrylate with Fe(0)/TsCl initiator system

Abstract: To obtain a high polymer coated Fe(0) surface, gas-phase-assisted surface polymerization (GASP) of methyl methacrylate (MMA) was investigated using a zerovalent iron (Fe(0))/p-toluene sulfonylchloride (TsCl) initiator system, resulting in successful high polymer production on the solid surface. GASP was found to be initiated by radical species that might have been generated via redox reactions with Fe(0), Fe(II), Fe(III), and TsCl. From 1 H-NMR analysis, the p-toluene sulfonyl group was found at one end of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…80,81 Solid-state grafting onto a carbon black surface has also been reported. Wu et al reported polymer grafting of natural rubber onto a carbon black surface via a solid-state method; this was achieved by trapping the natural rubber radicals formed in a Haake internal mixer.…”
Section: Discussionmentioning
confidence: 98%
“…80,81 Solid-state grafting onto a carbon black surface has also been reported. Wu et al reported polymer grafting of natural rubber onto a carbon black surface via a solid-state method; this was achieved by trapping the natural rubber radicals formed in a Haake internal mixer.…”
Section: Discussionmentioning
confidence: 98%
“…The confinement of the free‐radical sites at the end of the chains also prevents termination through steric effects, which creates living chain ends that extend upon exposure to more monomer, and that can be used to form block copolymers 35, 37. The preapplication of initiator prior to placing the substrate in the vacuum chamber for exposure to monomer vapors was also used to perform living radical polymerizations based on ATRP by gas‐phase assisted surface polymerization (GASP)40, 41 and nitroxide‐mediated radical polymerization by surface‐initiated VDP 39…”
Section: Unifying Themesmentioning
confidence: 99%
“…As compared to the continuous introduction of volatile initiators by iCVD and piCVD, preapplication of initiator fixes the available supply for film growth. Methods for CVD polymerization involving preapplication of the initiator include vapor‐phase assisted surface polymerization (VASP),35–38 living free‐radical polymerization methods such as nitroxide‐mediated polymerization (surface initiated vapor deposition polymerization (SI‐VDP))39 and atom transfer radical polymerization (ATRP) (also categorized as a form of gas‐phase assisted surface polymerization (GASP)),40, 41 anionic42 and cationic43–45 ring‐opening polymerization, cationic polymerization of acetylene derivatives,46 photoinitiated cationic polymerization of vinyl monomers,47 and ring‐opening metathesis polymerization (ROMP) (sometimes termed solventless polymerization) 46, 48, 49…”
Section: Introductionmentioning
confidence: 99%
“…The vapor phase‐assisted surface polymerization (VASP) method has been developed to coat many substrate surfaces with polymers, resulting in the prominent achievements of hydrophobic/hydrophilic controlling and surface grafting . It is an excellent method to preserve the delicate surfaces of materials due to the advantages of VASP process .…”
Section: Introductionmentioning
confidence: 99%